Effect of Service Quality and Trust on Revisiting Interest toward Customer Satisfaction - Lasmi Indaryani; Ririn Wulandari (International Journal of Management Science and Application, 2022)
The relationship between service providers and customers is an important component of various service businesses, and this study attempts to identify it. Service quality affects patients on return visits. A case study at Bunda Hospital Purwokerto serves as a quantitative methodology for this research, with 351 respondents randomly selected using the PLS-SEM 3.2.9 analysis tool. According to research findings, patient visits are positively influenced by trust and high-quality customer service. To increase patient interest in repeat visits, medical staff and public service quality must build a relationship of trust with patients. Medical services are intangible products with service quality and reliability to generate interest in repeat patient visits. To encourage patients' aspirations to return, medical facilities must increase their psychological confidence in the quality of their services.